Focus point: Geography - A Sea of Mirrors but where? : Will the Solar Energy Partnership between Europe and Africa contribute to an aggravation of regional disparities in Africa? - Schüssler, Frank; Justus Liebig University Giessen (My University, 2008)
In view of the current discussion about the threat of climate change and the increasing scarcity of fossil fuels, many groups, including politicians, entrepreneurs, journalists, and our inter-disciplinary working group arelooking to Africa for a future energy supply. At first glance, the potential for new energy forms from the long forgotten continent seems gigantic. There is a huge potential for wind farms, along the thinly settled coastalregions of western Morocco and the adjacent Republic of Sahara (occupied by Morocco), as well as Mauritania.The wind blows evenly and throughout the year as a result of the North East Trade Winds. Initially, the promise of solar thermal power facilities in North Africa seems particularly compelling especially as the energy potentialis 2-4 times greater than in central Europe. However, a careful evaluation of possible locations from an economic, ecological, and social perspective is of importance.
Keywords: ddc:550